Clinicopathological outcomes of microsatellite instability in colorectal cancer - ERGENÇ, MUHAMMER (My University, 2022)
Aims:This study aims to evaluate the histopathological features and prognostic parameters of tumors withmicrosatellite instability(MSI) compared with those without MSI in patients who underwent surgery forcolorectal cancer(CRC).Setting and Design:Follow-up for CRC at Istanbul Sultan 2. Abdulhamid Han Training and Research Hospital was retrospectively evaluated between March 2017 and March 2021.Methods and Material:The patients were divided into two groups: those with and without MSI. Groups were compared insurvivalparameters. As a secondary result, groups were compared in pathological parameters such as stage, tumor diameter, degree of differentiation, and lymphovascular, and perineural invasion.Statistical Analysis Used:Survivalcalculations were performed using the Kaplan–Meier analysis method. The effects of various prognostic factors related to tumor and patient characteristics on disease-free and overallsurvival(OS) were investigated by log-rank test.Results:Two hundred fourteen patients were analyzed. The median age of the patients was 66 (30–89), and 59.3% (n = 127) were male. There were 25 patients in the MSI group and 189 patients in the non-MSI group. We found that MSI tumors had a significantly higher differentiation degree than non-MSI tumors and larger tumor diameters. MSI tumors frequently settled in the proximal colon, and more lymph nodes were removed in the resection material. MSI tumors had longer disease-freesurvival, cancer-specificsurvival, and overallsurvival.Conclusions:By diagnosingmicrosatellite instability, CRCs can be divided into two groups. The histopathological features of the tumor and theprognosisof the disease differ between these groups. MSI can be a predictive marker in the patient’s follow-up and treatment.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)